Spatial investigation of technological choice and recycling in copper-base metallurgy of the South Caucasus - Ho, Joyce W. I.; Erb-Satullo, Nathaniel L. (Wiley, 2021)
Recent research has brought the prolific bronze industry of Bronze Age Colchis (modern western Georgia) into focus, but many aspects are still poorly understood. This study synthesises and re‐interprets legacy copper‐alloy compositional data to investigate technological choices and spatial patterning. It reveals a massive injection of fresh copper into the system during Late Bronze‐Early Iron Age, and a high degree of selectivity in the alloys used for different objects, with colour being as important as hardness in determining these choices. Spatial analyses show significant geographic variability in alloying practices, which map onto topographic zones in unexpected ways. We also explore recycling practices and argue that the term encompasses a range of different re‐use activities, which may be employed under differing economic conditions. Finally, the data suggest relatively extensive primary alloying of tin and copper in the Late Bronze and Early Iron Age, which further substantiates the speculation that some local tin sources were exploited.
Keywords: Metallurgy; Bronze Age; Technology; Spatial analysis; Legacy data; Caucasus; Black Sea